The Influence of Blockchain Technology and Digital Marketing on Banking Services: A Systematic Review - Tanoto, Keniciro Yamamoto; Prasiani, Ni Komang; Lestari, Putu Astri; Pratama, Putu Yogi Agustia (Program Pascasarjana UIN Sumatera Utara, 2025)
This study seeks to methodically analyze the impact of blockchain technology and digital marketing tactics on the enhancement of banking services in the digital age. Digital transformation necessitates that banks not only implement cutting-edge technologies to improve transaction efficiency and security but also establish robust contact with clients to foster loyalty and confidence. This study utilizes a Systematic Literature Review (SLR) methodology by examining 25 pertinent scientific articles from 2018 to 2024, sourced from prominent sources including Google Scholar, Scopus, and DOAJ. The study's findings demonstrate that blockchain facilitates the acceleration of service processes, improves transparency, and fortifies data security, whereas digital marketing substantially enhances customer engagement, satisfaction, and loyalty via personalized and educational communication strategies. The amalgamation of the two fosters a synergy that propels the advancement of efficient, trustworthy, and adaptive banking services tailored to the requirements of the digital generation. This research offers both theoretical and practical insights into banking service developments and acts as a reference for industry stakeholders and policymakers in advancing the digitization of the financial sector.